NIEZREALIZOWANA KODYFIKACJA PRAWA ŁUŻYCKIEGO NA ŚLĄSKU W POŁOWIE XIX STULECIA - Kruszewski, Tomasz (Zeszyty Prawnicze, 2016)
UNREALIZED CODIFICATION OF LUSATIA’S LAW IN SILESIA IN THE MID – 19TH CENTURY Summary The statement refers to designed codification of Lusatia’s law, which was in effect (from 1815) in Prussian Upper Lusatia up to that time. There had been Saxon law so far, which saved operative power after had being connected to the area of Prussia during deliberation of the Congress of Vienna. When law was sorted in Prussia in the mid – 19th century two schemes of codifications – the first for Silesia and the second for Upper Lusatia – were formulated in Silesian province, Upper Lusatia belonged to it. But after the Spring Peoples the possibility of sustaining principle of law’s particularism was refused. In that time development of the capitalist economic relationships included solidity of law in particular country and in that case the idea of possibility to in every provinces or in every cities could exist narrow legal norms relating to small area.